A redox mechanism underlying nucleolar stress sensing by nucleophosmin - Kai Yang (Nature Portfolio, 2016)
Nucleoplasmic translocation of NPM1 is integral to nucleolar stress sensing. Here, the authors show that nucleolar oxidation is a general cellular stress response, and that oxidation-related glutathionylation of NPM1 triggers its translocation and facilitates p53 activation.